Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Problem Based Learning (PBL) Pada Materi Elastisitas Untuk Melatih Kemampuan Berpikir Kritis - Aini, Misratul; Suhirman; Ali, Lalu Usman (CAHAYA: Journal of Research on Science Education, 2023)
This study aims to test the feasibility and test the effectiveness of Problem Based Learning (PBL) based Learner Worksheet (LKPD) to train students' critical thinking skills. This research uses the development method with the Borg & Gall model on students of class XI IPA at SMAN 1 Batukliang Utara. The data collection steps in this study are (1) research and data collection/information, (2) planning, (3) product design, (4) design validation, (5) design revision, (6) trial, (7) product revision. The results of this study are in the form of media expert validation results of 92.5% and categorized as "very feasible", material experts of 92.5% and categorized as "very feasible". As for the results of the validation of Physics subject teachers obtained results of 91% with the category " highly attractive ". While the development of PBL-based LKPD teaching materials is declared effective based on the response of students on the indicators of the assessment instrument in the form of a questionnaire after the trial by obtaining a percentage of 91% with the category " highly attractive ".